Correction of Class II Division 2 Deepbite Malocclusion with Non-extraction Therapy - Shrestha, Situ L; Manipal, Supreeth S; Shrestha, Bikash V; Jaiswal, Alok K (Orthodontic Journal of Nepal, 2013)
The article presents a case report of a teen age girl with Class II Division 2 malocclusion with deep over bite. The case was treated on non-extraction basis using 0.018 pre-adjusted edgewise appliance with anterior bite plate (monobloc) to correct deep bite and forward placement of the mandible. Use of Class II elastics helped to achieve Class I canine and molar retention. Treatment was completed in 22 months with good occlusion and facial esthetics. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9287 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 73-75